Autologous porcine VRAM flap model for VCA research - Blades, Caitlin M.; Dumanian, Zari P.; Wang, Yong; Wang, Zhaohui; Li, Bing; Washington, Kia M.; Slade, Julia B.; Evans, Conor L.; Arrowsmith, Paula; Farkash, Evan A.; Yu, Jason W.; Greyson, Mark A.; et al. (Frontiers in Transplantation, 2024)
IntroductionAs research advances in vascularized composite allotransplantation (VCA), large animal models are essential for translational studies related to immune rejection and graft survival. However, procurement of large flaps can cause significant defects, complicating wound closure and increasing postoperative risks. This study details the surgical techniques and outcomes of autologous vertical rectus abdominis myocutaneous (VRAM) flap transplantation and neck flap isolation with induced ischemia in a swine model. The purpose of this study was to identify the most effective control procedure for use in future VRAM flap allotransplantation research.MethodsWe performed two left heterotopic autologous VRAM flap transplants and two right anterolateral neck flap isolations using female Yucatan pigs. Postoperatively, animals were monitored for complications and flap healing, with punch biopsies taken on POD1, 5, and at the end of the study for histological analysis. Transcutaneous oxygen and temperature were also recorded.ResultsBoth autologous flaps survived after vessel anastomosis, with effective closure of abdominal defects using suturable mesh, and no postoperative complications were observed. Histology revealed mild dermal edema and perivascular inflammation on POD5. In the neck flap group, both flaps survived temporary ischemia, however, postoperative complications included dorsal flap necrosis and wound dehiscence, requiring reoperation. No gross inflammation or edema was observed following surgery and histologically there was only mild dermal edema on POD5.DiscussionWe have developed a low-risk, technically feasible porcine autologous VRAM flap transplantation model and our findings support its use in future VCA studies.